Determinants of Foreign Direct Investment from China to Indonesia - Mansur, Amin (Research of Economics and Business, 2023)
This study identifies and analyzes the determinants influencing China's foreign direct investment level in Indonesia. The independent variables in this study are economic growth, inflation rate, wage rate, exchange rate, and export value. The data used is time series data from 2000 - 2016. The analytical method used is multiple linear regression. The study results show that wage and inflation rates significantly affect the foreign investment level from China to Indonesia. The variables of economic growth, exchange rates, and exports do not affect the level of foreign investment from China to Indonesia. The simultaneous test results significantly influence all the independent variables used in this study. The implication for foreign direct investment is that the government must increase foreign investment in Indonesia to increase economic growth by improving the investment climate in the country by providing several facilities to assist foreign investors so that investors feel safe investing their capital in Indonesia and with synergy with monetary policy in lowering interest rates to increase investor interest in investing.